MATHEMATICS LEARNING PROCESS AND RESULTS OF ELEMENTARY SCHOOL STUDENTS IN LIMITED FACE-TO-FACE LEARNING - Ariani Haffidah Lestari; Ratnasari Diah Utami (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
The  aim of the research is to analyze the learning process and the learning outcomes of students in limited face-to-face learning. The research method used was descriptive qualitative, the research subjects were class V teachers and fifth grade students. The research instruments used were interview text, observation, documentation. The validity of the data obtained was tested using the triangulation test, and the analysis process used the Miles and Huberman model, namely data reduction, data presentation and conclusion. The results of the study show that the implementation of limited face-to-face learning at elementary school is carried out in compliance with health protocols. The learning process in the classroom the teacher explains the material briefly, concisely and clearly, after that gives examples of practice questions to students. In the learning activities the teacher uses the talking stick learning method, lectures and explanations of sample questions. The learning activities in the class are quite active, and the learning outcomes achieved by students have been able to reach the specified KKM. However, in the learning process it is still teacher center, so it needs to be developed into a student center so that the learning process is more meaningful for students. So that students are given the freedom to explore knowledge independently more deeply and improve self-quality.